Konstruksi Sufistik Pendidikan Multikultural Universitas Yudharta Pasuruan - Syaifuddin, Helmi; Salis, Rahmatullah; Mafrudlo, Ahmad Mahfudzi (Universitas Islam Negeri Mataram, Indonesia, 2020)
The aim of this research is to comprehensively understand the sufistic construction and the construction patterns of Sufistic values ??in multicultural education. This study uses a qualitative method which stand on Peter L.Berger's social construction theory. The results of this study is that the construction, took place at the University of Yudharta Pasuruan was assisted by the vision and mission of the tertiary institution which became the perspective of the performance of the entire academic communities. On the other hand it is also based on understanding, awareness and transformation of knowledge. The dialectical entity of social construction theory runs perfectly, the entities are Externalization, Objectivation, and Internalization. Multicultural activities and behaviors are formed by and on the basis of mutually agreed understanding of religious texts, the teachings of the tarekat and the transformation of science in the classroom. The construction process which consists of habituation, institutionalization, and legitimacy helps the implementation of all multicultural behaviors and activities of the academics of Yudharta Pasuruan University. Tujuan dari penelitian ini adalah untuk mengetahui secara comprehensive konstruksi sufistik dan pola konstruksi nilai-nilai sufistik dalam pendidikan multikultural. Penelitian ini menggunakan metode kualitatif berdasarkan teori konstruksi sosial Peter L.Berger. Hasil dari penelitian ini adalah bahwa konstruksi yang terjadi di Universitas Yudharta Pasuruan dibantu oleh visi misi perguruan tinggi yang menjadi cara pandang kinerja seluruh civitas akademika. Di lain hal juga didasarkan dari pemahaman, kesadaran dan transformasi ilmu. Entitas dialektika teori konstruksi sosial berjalan dengan sempurna, entitas tersebut adalah Eksternalisasi, Objektivasi, dan Internalisasi. Aktifitas dan perilaku multikultural terbentuk oleh dan atas dasar pemahaman yang disetujui bersama dari teks agama, ajaran tarekat dan transformasi ilmu di dalam kelas. Proses konstruksi yang terdiri dari pembiasaan, institusionalisasi, dan legitimasi membantu implementasi seluruh perilaku dan aktifitas multikultural para civitas akademika Universitas Yudharta Pasuruan.